Coordination modes of pyridine-carboxylic acid derivatives in samarium (III) complexes - Soares-Santos, Paula C. R. (2006)
Samarium (III) complexes of picolinic acid (Hpic), 3-hydroxypicolinic acid (HpicOH) and 2-hydroxynicotinic acid (H2nicO) were prepared and characterised. The crystal structures of the samarium complexes K2[Sm2(pic)6(l-pic)2] Æ 7.5H2O (1), [Sm(picOH)2- (l-HpicO)(H2O)] Æ 3H2O (2) and [Sm(HnicO)2(l-HnicO)(H2O)] Æ 5H2O (3) were determined by single-crystal X-ray diffraction studies. The coordination modes of the pyridine-carboxylic acids to Sm3+ centres have been investigated. These complexes showed roomtemperature photoluminescence.